Knowing too little or too much: the effects of familiarity with a co-performer's part on interpersonal coordination in musical ensembles - Ragert, Marie; Schroeder, Tim; Keller, Peter E. (Frontiers in Psychology, 2013)
Expert ensemble musicians produce exquisitely coordinated sounds, but rehearsal is typically required to do so. Ensemble coordination may thus be influenced by the degree to which individuals are familiar with each other’s parts. Such familiarity may affect the ability to predict and synchronize with co-performers’ actions. Internal models related to action simulation and anticipatory musical imagery may be affected by knowledge of (1) the musical structure of a co-performer’s part (e.g., in terms of its rhythm and phrase structure) and/or (2) the co-performer’s idiosyncratic playing style (e.g., expressive micro-timing variations). The current study investigated the effects of familiarity on interpersonal coordination in piano duos. Skilled pianists were required to play several duets with different partners. One condition included duets for which co-performers had previously practiced both parts, while another condition included duets for which each performer had practiced only their own part. Each piece was recorded six times without joint rehearsal or visual contact to examine the effects of increasing familiarity. Interpersonal coordination was quantified by measuring asynchronies between pianists’ keystroke timing and the correlation of their body (head and torso) movements, which were recorded with a motion capture system. The results suggest that familiarity with a co-performer’s part, in the absence of familiarity with their playing style, engenders predictions about micro-timing variations that are based instead upon one’s own playing style, leading to a mismatch between predictions and actual events at short timescales. Predictions at longer timescales—that is, those related to musical measures and phrases, and reflected in head movements and body sway—are, however, facilitated by familiarity with the structure of a co-performer’s part. These findings point to a dissociation between interpersonal coordination at the level of keystrokes and body movements.